Article THE FUNCTIONS OF THE CASE IN THE USE OF GERMAN VERBS : THE FUNCTIONS OF THE CASE IN THE USE OF GERMAN VERBS - Inomov, Ural (Журнал иностранных языков и лингвистики, 2021)
The authors of the article consider the functions of the dative case in the use of German verbs not just in structural, but in structurally functional models of sentences, so they tried to consider them in a somewhat graduated manner, depending on the increase in the quantitative side of the sentence models.